Adoption Green Car in Indonesia : Implementation VBN Theory - Akbar, A Zaenudin; Kuswati, Rini (PT Inovasi Pratama Internasional, 2024)
Electric cars have the potential to reduce greenhouse gas emissions and air pollution compared to fossil fuel cars. In green behavior research, a focus on electric cars can provide a better understanding of the preferences, motivations, and challenges individuals face in switching to these environmentally friendly cars. This research aims to analyze the influence of biospheric values ​​on ascription of responsibility and willingness to adopt, analyze the influence of ascription of responsibility on personal norms and willingness to adopt, analyze personal norms on willingness to adopt and personal norms mediate the influence of ascription of responsibility on willingness to adopt. This research data was collected using a questionnaire because this research is research using quantitative methods. Data analysis in this research was carried out using the Partial Least Square (PLS) method using SmartPLS software version 3.0. The results of this research show that Biospheric Value has a significant positive effect on interest in adopting electric cars. Ascription Of Responsibility has a significant positive effect on Personal Norm. Biospheric Value has an insignificant negative effect on Willingness To Adopt. Ascription Of Responsibility has a significant positive effect on Willingness To Adopt. Personal Norm has a significant positive effect on Willingness To Adopt. Personal Norms can mediate the influence of Ascription Of Responsibility on Willingness To Adopt.